Is there any association between GLY82 ser polymorphism of rage gene and Turkish diabetic and non diabetic patients with coronary artery disease? - İSBİR, CEMİL SELİM (SPRINGER, 2012)
This study was carried out in 52 non-diabetic, 62 diabetic patients with coronary artery disease (CAD) and 55 controls. A Gly to Ser change RAGE gene was analyzed by PCR-RFLP techniques. GlyGly genotype frequency is higher in non-diabetics versus controls (P < 0.001). GlySer frequency is higher in diabetics than controls and non-diabetics (P < 0.001). Ser allele frequency is respectively increased in the order of diabetics > Controls > non-diabetics. These results reveals none association between Gly82Ser and the development of disease in non-diabetic patients. In diabetics with Ser allele, higher prevalence of left-ventricule-hypertrophy was observed, but the significant difference between Gly82Ser and left-ventricule-hypertrophy only found in the whole patient group. As a result Ser allele has much more importance in the development of left-ventricule-hypertrophy than other cardiovascular risk factors. In this study we found the presence of Gly allele contributes to the CAD in non-diabetics and Ser allele may contribute to disease in diabetics.
Keywords: RAGE; Coronary artery disease; Diabetes mellitus; Polymorphism; Genetics; GLYCATION END-PRODUCTS; RECEPTOR; ATHEROSCLEROSIS; INFLAMMATION; DYSFUNCTION